THE INFLUENCE OF GOOGLE SCHOLAR INDEXATION ON CAREER DEVELOPMENT AND LECTURER PERFORMANCE IN HIGHER EDUCATION - Axelon S Renyaan; Ainil Mardiah; Aslan Aslan (Adisam Publisher, 2025)
This study aims to analyse the effect of Google Scholar indexation on the career development and performance of lecturers in higher education. Indexation in Google Scholar allows lecturers' academic work to be more accessible and recognised by the global community, which has an impact on increasing the number of citations and h-index. These metrics are often used as indicators in performance evaluation, promotion, and incentivisation in the academic environment. In addition, the visibility gained through indexation increases opportunities for research collaboration with other researchers, both at the national and international levels. The results show that Google Scholar indexation plays an important role in supporting lecturers' career recognition and development, and contributes positively to improving their performance, both in research and teaching. Thus, Google Scholar indexation not only strengthens lecturers' academic careers, but also supports efforts to improve the quality of education in higher education.